Land Acquisition for Infrastructure Development with the Mechanism of Government Cooperation with Business Entities (KPBU): Case Study of Lhok Guci KPBU Project - Kurdi; Syafitri, Cut Zulfahnur (Ajudikasi : Jurnal Ilmu Hukum, 2024)
This research discusses land acquisition for infrastructure development through the mechanism of Government Cooperation with Business Entities (PPP) with a case study of the Lhok Guci PPP project. Land acquisition is a crucial stage in PPP that often faces various legal, social, and economic challenges. This research uses a normative juridical method to analyze relevant regulations and a conceptual approach to understand key concepts. The stages of land acquisition studied include planning, location determination, implementation, compensation, release of rights, granting land rights, and supervision. The Lhok Guci case study shows the importance of transparency and coordination between relevant parties for the success of PPP projects. The results of the study are expected to improve the efficiency of the land acquisition process in future infrastructure projects.